Laser Cladding of Fe-based Metallic Glass/MoS2 Self-lubricating Composites: Effect of Power and Scanning Speed - Giroto,Giovana (2017)
MoS2 powder has been used to form "self-lubricating" composite coatings, which are very useful to increase the lifetime of machines where liquid lubricants cannot be used. In this work, amorphous overspray powder of Fe60Cr8Nb8B24 (at%) alloy was mixed with 5wt.% MoS2 powder and it was used to produce single tracks on AISI 1020 steel substrates by laser cladding. The tracks were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), differential scanning calorimetry (DSC) and Vickers microhardness. It was observed α-Fe, an Nb-rich intermetallic and MoS2 particles in the tracks, regardless of laser parameter used. DSC analyses proved the presence of amorphous phase for samples produced with parameters 200W/33.3mm/s, 600W/100mm/s, 800W/100mm/s and 800W/150mm/s. The tracks produced with larger power (800W) and higher scanning speeds (100 and 150mm/s) exhibited a better integrity and homogeneity, lower dilution and presence of amorphous phase, being these parameters considered the most appropriate to produce composite coatings of Fe60Cr8Nb8B24 (at%)/5wt% MoS2 containing amorphous phase. Hardness tests showed that the single tracks produced are harder than the substrate, for example, the track produced with 800W/150mm/s exhibits hardness six times higher than the steel substrate, 1200 HV0.3 and 200 HV0.3, respectively.